CEACAM1 regulates integrin αIIbβ3-mediated functions in platelets. (17th February 2016) - Yip, Jana; Alshahrani, Musaed; Beauchemin, Nicole; Jackson, Denise E.
Abstract: Previous studies have implicated that the Ig-ITIM superfamily member, CEACAM1 may regulate integrin function. While CEACAM1 has been demonstrated to play a role as an inhibitory co-receptor of ITAM-associated GPVI/FcR γ-chain signaling pathways in platelets, its physiologic role in integrin αIIbβ3-mediated platelet function is unclear. In this study, we investigate the functional importance of Ceacam1 in murine platelets. We show that CEACAM1 is constitutively associated with integrin αIIbβ3 in resting human and mouse platelets as demonstrated by co-immunoprecipitation studies. Using Ceacam1 -deficient mice, we show that they have prolonged tail bleeding times and volume of blood lost that is corrected by reconstitution with platelet Ceacam1. Ceacam1 − / − platelets have moderate integrin αIIbβ3 mediated functional defects with impaired kinetics of platelet spreading on fibrinogen and failure to retract fibrin clots in vitro . This functional integrin αIIbβ3 defect could not be attributed to altered integrin αIIbβ3 expression. Ceacam1 −/− platelets displayed normal "inside–out" signaling properties as demonstrated by normal agonist-induced binding of soluble (fluorescein isothiocyanate) FITC-fibrinogen, JON/A antibody binding, and increases in cytosolic free calcium levels. This study provides direct evidence that Ceacam1 is essential for normal integrin αIIbβ3-mediated platelet function and that disruption of mouse Ceacam1 induced moderate integrin αIIbβ3-mediated functional defects.